Synthesis and evaluation of cerebroprotective activity of novel 6,7-dimethoxyquinazolin-4(3H)-one derivatives containing residues of amino acids and dipeptides - Alexey S. Chiriapkin; Ivan P. Kodonidi; Dmitry I. Pozdnyakov (Chimica Techno Acta)
Neurodegenerative processes of the central nervous system are an important socially significant problem of modern society. They cause many diseases, such as Alzheimer's disease and cerebral ischemia, which significantly reduce the quality of human life and can lead to disability or death. The aim of this study was to synthesize novel 6,7-dimethoxyquinazolin-4(3H)-one derivatives with the remains of neuroactive amino acids and dipeptides in order to investigate their cerebroprotective properties. As a result of the study, 13 novel 6,7-dimetho-xyquinazolin-4(3H)-one derivatives were synthesized. Cerebral ischemia in rats was reproduced by irreversible right-sided occlusion of the middle cerebral artery using the Tamura method, and the area of brain necrosis was evaluated. Cognitive functions were evaluated in the Y-maze test. Among the studied quinazolinone derivatives, compounds 3i, 3j and 3k have the most pronounced cerebrotropic activity, which is not inferior to ethylmethylhydroxypyridine succinate in terms of pharmacological activity, making them promising objects for further research.